Optimal parameters of motorcycle instrument panels design for the elderly by using fuzzy logic. (August 2016) - Liang, Yo-Wen; Lee, An-Sheng; Liu, Shuo-Fang
Abstract: This study investigates the optimal interface design of motorcycle instrument panels for the elderly. Elements such as needle length, needle width, and minimum needle scale unit that constitute 125 types of motorcycle instrument panel designs were investigated. There were 36 participants selected for this study who used motorcycles as their primary mode of transportation. Their cognitive errors in reading speedometers and fuel meters as well as the required task time and their general satisfaction levels were measured. Finally, the data were translated into fuzzy numbers and the similarity was analyzed to select optimal design parameters. Based on our research, the optimal design for the speedometer needle dimensions were 4.5 cm long, 2 mm wide with a minimum scale unit of 20 scale marks. The optimal design for the fuel meter needle dimensions was determined to be 3.5 cm long, 1.5 mm wide, and with a minimum scale unit of 20 scale marks.